Enablers and barriers for the provision of community‐based HCV treatment: A case study of a real‐world practice. Issue 5 (3rd February 2020) - Pourmarzi, Davoud; Smirnov, Andrew; Hall, Lisa; Thompson, Hayley; FitzGerald, Gerard; Rahman, Tony
Abstract: Background: Although the availability of fully funded direct‐acting antivirals (DAAs) and the eligibility of primary care providers (PCPs) to provide hepatitis C virus (HCV) have removed barriers related to access to hospital‐based HCV treatment in Australia, there are still many barriers to the provision of HCV treatment in community settings. There is a lack of knowledge regarding the barriers to, and enablers of HCV treatment in community settings in Australia. This study aimed to identify barriers and enablers for the provision of community‐based HCV treatment. Methods: This study was a part of a mixed‐method case study of the Cure‐It programme. The programme was studied to better understand barriers and enablers experienced by stakeholders of such programmes. The programme is delivered through the Prince Charles Hospital in Brisbane, Australia, and aimed to improve access to HCV treatment in community settings. Data were collected using semi‐structured interviews with 12 healthcare providers and nine patients between July and December 2018. Purposive sampling was used to ensure diverse views were captured. The interview transcripts were analysed using inductive thematic analysis. Results: Ease of access to specialist support, easy and high value treatment, co‐location with or providing other services and motivated patients enabled PCPs to be engaged with the Cure‐It programme. Several interconnected factors related to patients' characteristics and health system acted synergistically to enable patients to initiate and complete treatment. These included a desire to remove HCV as a source of shame, having children, awareness of HCV consequences, access to DAAs for free, ease of access to general practices and drug and alcohol services, and access to a safe and enabling environment. The identified barriers were interconnected at the levels of patients, PCPs and primary care systems and acted synergistically to prevent patients and PCPs from becoming engaged with HCV treatment. PCPs' related barriers included a lack of knowledge, their perception of HCV as a specialist area and of patients with HCV as 'hard to manage' patients along with the practice preferences and priorities. Patients' related barriers included their socioeconomic characteristics, internalized stigma, perception of not being sick and lack of knowledge. Additionally, the unavailability of support for patients and existence of stigma in primary health care, along with poor communication between the hospital and primary care system, and the unavailability of FibroScan ® in primary care discouraged PCPs and patients engagement specifically with the provision of community‐based HCV treatment. Conclusion: Various strategies are needed to improve PCPs and patients' knowledge and awareness of HCV treatment. Training and support for PCPs need to be easy to access and should cover both clinical and social aspect of HCV. Connecting PCPs to other related services may improve PCPs' and patients' engagement with HCV treatment.